DAILY CONTROL MODERATES STRESS REACTIVITY AND BECOMES INCREASINGLY IMPORTANT WITH AGE - Koffer, R. (Innov Aging, 2017)
This study examines how associations among daily stress processes and negative affect are related to both between- and within-person control beliefs across the adult lifespan. Analyses included participants from the Intraindividual Study of Affect Health and Interpersonal Behavior, with N=150 adults aged 18–89 assessed over T=63 days. Multilevel models indicated that both lower levels of general control beliefs and days with lower daily control beliefs are associated with greater stressor reactivity. The association between stressor reactivity and daily control beliefs is particularly strong for those who experience generally higher levels of stressor exposure. Older adults appear to be more vulnerable to the association between daily control beliefs and stressor reactivity. We will discuss the theoretical importance of including multi-time-scale risk and resilience factors when examining the links between stress and well-being.